The SWOT Analysis In Improving Consumers In Lazada Indonesia E-Commerce - Cici Winda Atila Atila; Minta Ito Lubis; Nurbaiti Nurbaiti (Penerbit Jurnal Indonesia, 2021)
This study aims to analyze the e-commerce system in the largest marketplace in Indonesia. The sample in this study is Lazada Indonesia. The research used is a qualitative method. The research conducted includes a SWOT analysis on the Lazada Indonesia company. The results of the analysis of this study show that Lazada Indonesia can become the largest online shopping company in Indonesia, with advantages such as complete products sold, free shipping provided and easy shopping at Lazada Indonesia. But lazada also still has weaknesses regarding system security and the many cases of fraud involving consumers. Lazada's goal is to become the most popular and well-known online shopping company in Indonesia and provide the best service for consumers in their shopping needs.